Nitrate regulation of lateral root and root hair development in plants. (4th December 2019) - Liu, Bohan; Wu, Junyu; Yang, Shuaiqi; Schiefelbein, John; Gan, Yinbo
Abstract: Nitrogen (N) is one of the most important macronutrients for plant growth and development. However, the concentration and distribution of N varies in soil due to a variety of environmental factors. In response, higher plants have evolved a developmentally flexible root system to efficiently take up N under N-limited conditions. Over the past decade, significant progress has been made in understanding this form of plant 'root-foraging' behavior, which is controlled by both a local and a long-distance systemic nitrate signaling pathway. In this review, we focus on the key components of nitrate perception, signaling, and transduction and its role in lateral root development. We also highlight recent findings on the molecular mechanisms of the nitrate systemic signaling pathway, including small signaling peptides involved in long-distance shoot–root communication. Furthermore, we summarize the transcription factor networks responsible for nitrate-dependent lateral root and root hair development. Abstract : This review provides an update on the molecular mechanisms involved in the long-distance shoot–root communication in systemic nitrate signaling, and outlines the transcription factor network responsible for nitrate regulation of lateral root and root hair growth.